Eleven rings the soul of success - Jackson, Phil; Delehanty, Hugh 1949- (Penguin Books, 2014)
The head coach of the Chicago Bulls and Los Angeles Lakers traces the life experiences and philosophies that inspired his championship-winning techniques, revealing how he forged successful teams by combining talents and promoting trust.